Koordinasi Perencanaan Sektoral Dan Regional Dalam Perencanaan Infrastruktur Pariwisata Di Kawasan Taman Nasional Gunung Leuser (TNGL) Bukit Lawang Kabupaten Langkat Sumatera Utara - Imanda Isra Andini; Mohammad Ridwan (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
The development of the tourism sector that is carried out properly will have an impact on the economic sector and encourage development for other sectors. This study aims to determine and describe the Coordination of Sectoral and Regional Planning in Tourism Infrastructure Planning in the Bukit Lawang TNGL area, Kabupaten Langkat, North Sumatra. The research method used in this research is descriptive qualitative. Data collection techniques were carried out through interviews and observations as well as documentation and literature. The results showed that the Coordination of Sectoral and Regional Planning in Tourism Infrastructure Planning in the Bukit Lawang TNGL area, Kabupaten Langkat, North Sumatra has not run optimally. This is because the tourism infrastructure is still not optimal in developing Bukit Lawang tourism at this time.